2018
DOI: 10.1016/j.foodres.2018.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted extraction of phenolic compounds from four economic brown macroalgae species and evaluation of their antioxidant activities and inhibitory effects on α-amylase, α-glucosidase, pancreatic lipase and tyrosinase

Abstract: Four economically important brown algae species (Ascophyllum nodosum, Laminaria japonica, Lessonia trabeculate and Lessonia nigrecens) were investigated for phenolic compound extraction and evaluated for their antioxidant, anti-hyperglycemic, and pancreatic lipase and tyrosinase inhibition activities. Microwave assisted extraction (MAE) at 110 °C for 15 min resulted in both higher crude yield and higher total phenolic content (TPC) for all algae species compared with those obtained by conventional extraction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(108 citation statements)
references
References 38 publications
2
106
0
Order By: Relevance
“…Microwave radiation can also stimulate cuticular layer destruction which was observed as very rough algae surface with many cavities after high pressure (120 psi) MAE application [56]. MAE has been successfully used for isolation of various bioactive compound from seaweeds [57][58][59][60] as well as polysaccharides from other plants [61][62][63]. Application of MAE for brown APS extraction is summarized in Table 2 along with its effect on chemical structure and bioactivities of target polysaccharides.…”
Section: Advanced Extraction Techniquesmentioning
confidence: 99%
“…Microwave radiation can also stimulate cuticular layer destruction which was observed as very rough algae surface with many cavities after high pressure (120 psi) MAE application [56]. MAE has been successfully used for isolation of various bioactive compound from seaweeds [57][58][59][60] as well as polysaccharides from other plants [61][62][63]. Application of MAE for brown APS extraction is summarized in Table 2 along with its effect on chemical structure and bioactivities of target polysaccharides.…”
Section: Advanced Extraction Techniquesmentioning
confidence: 99%
“…Table 4 summarizes the studies concerning the MAE extraction of phenolic compounds from macroalgae. Ethanol:water mixtures have been the most commonly used in MAE of phenolic compounds from macroalgae [108,109], although few authors have applied acetone:water mixtures [54], methanol:water [110], or just water [111]. Pérez et al studied and optimized the MAE of phenolic compounds from Sargassum muticum wet samples in two stages, with a solvent-free extraction followed by a water extraction, adding only the moisture content [112].…”
Section: Microwave-assisted Extractionmentioning
confidence: 99%
“…Again, most studies concerning the MAE of phenolic compounds from macroalgae have not characterized the extracts obtained, revealing a major weakness in these works. However, a recent study showed that this technique is able to extract different families of phenolic compounds, including phenolic acids, flavonoids, and phlorotannins from different brown macroalgae species [110], which point out that MAE may be a promising technique when the whole phenolic fraction of macroalgae is intended for study.…”
Section: Solvent Of Extraction (mentioning
confidence: 99%
“…In addition, MAE extraction is very suitable for extracting compounds that are not heat resistant (Angiolillo et al, 2015). The MAE method can also help to increase the amount of crude extract in the extraction time and the lower amount of solvent compared to conventional extraction methods (Vinatoru et al, 2017;Yuan et al, 2018;Zhong et al, 2018). In the MAE method, the microwave generated can increase the temperature of the solvent in the material which can cause the cell wall to break and the substances contained in the cell out towards the solvent, so that the yield produced increases (Chemat and Giancarlo, 2013).…”
Section: Original Researchmentioning
confidence: 99%